An Evolutionary and Environmental Perspective of the Interaction of Nanomaterials with the Immune System-The Outcomes of the EU Project PANDORA - Boraschi, Diana (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The book collects scientific contributions aiming at describing the common mechanism, across living species, by which innate immunity interacts with nanomaterials with the goal of harnessing such interactions for improving environmental and human safety and exploiting them for modulating immunity in vaccination strategies.